ENVIRONMENTAL VULNERABILITIES INDEX FORMULATION IN FRAGILE ECOSYSTEM OF THE INDIAN SUNDARBANS - Das, Pritha; Das, Atin (MATTER: International Journal of Science and Technology, 2017)
Human Development Index (HDI) defined by United Nations Development Programme (UNDP) involves health, education and life standard. HDI as a measurement of development for a community is realistic as it takes into account the condition of common people’s livelihood. Here, we study the development of Sundarbans in South and North 24 Parganas districts of West Bengal. Existing data indicates poor infrastructure as well as horrifying poverty, but livelihood, education and health indices for all 19 blocks of Sundarbans do not depict the exact developmental scenario. Climatic shocks reinforce risks and environmental vulnerabilities (EV) leading to long term setback for the human development. EV affects the developmental status and thus modifies HDI. In this work, we propose to take into account the EV. We present through review of existing data and literature related to human development, HDI, show anomalies in the available data and discuss factors of EV. Finally, we propose a model to formulate Environmental Vulnerability Index (EVI) for Sundarban using model of 4 dimensions with 24 indicators expressed in terms of 120 variables given below. We demonstrate here how to collect EVI using values of variables through house hold survey as well as available secondary data.